2011
DOI: 10.1215/00127094-1384809
|View full text |Cite
|
Sign up to set email alerts
|

Explicit constructions of RIP matrices and related problems

Abstract: Abstract. We give a new explicit construction of n × N matrices satisfying the Restricted Isometry Property (RIP). Namely, for some ε > 0, large N and any n satisfying N 1−ε ≤ n ≤ N , we construct RIP matrices of order k ≥ n 1/2+ε and constant δ = n −ε . This overcomes the natural barrier k = O(n 1/2 ) for proofs based on small coherence, which are used in all previous explicit constructions of RIP matrices. Key ingredients in our proof are new estimates for sumsets in product sets and for exponential sums wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
233
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(234 citation statements)
references
References 38 publications
0
233
0
1
Order By: Relevance
“…The following proposition [9] relates the RIP constant δ k and μ. Candes [2] has shown that whenever φ satisfies RIP of order 3k with δ 3k < 1, the CS reconstruction error satisfies the following estimate…”
Section: Definitionmentioning
confidence: 99%
“…The following proposition [9] relates the RIP constant δ k and μ. Candes [2] has shown that whenever φ satisfies RIP of order 3k with δ 3k < 1, the CS reconstruction error satisfies the following estimate…”
Section: Definitionmentioning
confidence: 99%
“…Coherence plays a central role in the sensing matrix construction, because small coherence implies the RIP [9]. In the early work of compressed sensing, the entries of the sensing matrix are generated by an independent identically distributed (i.i.d.)…”
Section: Introductionmentioning
confidence: 99%
“…Additive combinatorics also has important applications in e-voting [77,220]. Recently, Bourgain et al [51] gave a new explicit construction of matrices satisfying the Restricted Isometry Property (RIP) using ideas from additive combinatorics. RIP is related to the matrices whose behavior is nearly orthonormal (at least when acting on sufficiently sparse vectors); it has several applications, in particular, in compressed sensing [71,72,73].…”
Section: Introductionmentioning
confidence: 99%